Detection of inducible clindamycin resistance among staphylococcus isolated from patients attending a tertiary care hospital in South India - Saranya Mallamgunta; K H Vasudeva Naidu; Nukanaboina Ramakrishna (Journal of Clinical and Scientific Research, 2020)
Background: Resistance to antimicrobial agents led to the usage of macrolide-lincosamide-streptogramin B (MLSB) family to treat staphylococcal infection. Methods: One hundred and ninety one isolates obtained from various clinical samples such as pus, wound, swab, blood urine, and other body fluids were processed, and staphylococci were isolated as per standard bacteriological techniques. The antibiotic sensitivity was tested by Kirby–Bauer disc-diffusion method. Results: Out of 191 isolates, 32% were coagulase-negative staphylococci (CoNS). Of these, 48% and 65% were resistant to erythromycin, respectively. Among erythromycin-resistant S. aureus, 30% each showed constitutive resistance and inducible clindamycin (CL) resistance, and 60% showed MS phenotypes by the D-test. Of the CoNS, 18% showed inducible CL resistance. Among 130 S. aureus isolated, 15% each had constitutive macrolide-lincosamide-streptogramin B resistance (MLSBc), inducible macrolide-lincosamide-streptogramin B resistance (MLSBi) and 25 (19%) were D test-negative, were resistant to macrolides, streptogramins, sensitive to lincosamides. Among 61 CoNS isolated 9 (15%) were MLSBc resistant, 7 (11%) were MLSBi resistant and 24 (39%) were D-test negative (MS phenotype). Resistance MLSBi percentage was more among S. aureus 15% compared to CoNS 11%. Conclusions: The ER-CL disc-approximation test (D-test) emerged as a simple, auxiliary, easy to perform, reliable method and can be used as routine laboratory method for detecting inducible, constitutive and MS phenotypes.